INVITATIONAL RHETORIC: ALTERNATIVE RHETORICAL STRATEGY AS ECOFEMINIST PRACTICE FOR TRANSFORMATION OF PERCEPTION AND USE OF ENERGY IN THE RESIDENTIAL BUILT ENVIRONMENT FROM THE KEWEENAW TO KERALA - MERLE KINDRED
This paper explores the viability of invitational rhetoric as a mode of advocacy for sustainable energy use in the residential built environment. The theoretical foundations for this study join ecofeminist concepts and commitments with the conditions and resources of invitational rhetoric, developing in particular the rhetorical potency of the concepts of resourcement and enfoldment. The methodological approach is autoethnography using narrative reflection and journaling, both adapted to and developed within the autoethnographic project.